High-speed gas injector for powerful plasmadynamic systems - Staltsov, V.V.; Chebotarev, V.V.; Makhlaj, V.A. (Вопросы атомной науки и техники, 2015)
The paper describes the design features of gas injectors for the axial (parallel to the axis of the accelerator) and radial (perpendicular to the axis of the accelerator) working gas supply into the accelerator channel. The results of gas-dynamic studies of the injectors are presented. The amount of the working gas inlet was investigated as a function of gas pressure under the blocking valve element. A strong dependence of the amount of the injected working gas on the current value in the control coil was found.